Penerjemahan Video Dakwah Syekh Nabil Al-Awadi: Analisis Kesalahan Fonetik Artikulatoris-Auditoris : The Translation of Sheikh Nabil Al-Awadi's Da'wah Video: An Analysis of Articulatory-Auditory Phonetic Errors - Nisa', Mauidlotun; Jannah, Fisqiyah Raudhatul (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2024)
This research aims to reveal the phonetic errors heard and pronounced by several students, and to identify the distribution of phonetic errors in Sheikh Nabil Al-Awadhi's sermon videos. This research is a qualitative-descriptive and library research with a communicative translation approach focused on auditory phonetic analysis. The primary data for this research are the sermon videos on Sheikh Nabil Al-Awadhi's YouTube channel titled